The Contribution of the Institute of Slavic Studies, Polish Academy of Sciences to the Development of the Clarin-PL Infrastructure: Examples of Corpus Analysis of the Vocative Case - Roszko, Danuta; Roszko, Roman (Slavic Languages Today: Categories, Structures and Processes, 2021)
This article describes multilingual corpora with Polish as the hub language which have been constructed by a team of linguists from the Institute of Slavic Studies, Polish Academy of Sciences. The first part (Sections 1–3) outlines the factors which led to the development of corpus linguistics studies at the Institute and presents its first corpora. Section 4 provides an overview of the Clarin infrastructure and the multilingual corpora of Slavic and Baltic languages which were designed under this framework by a team working at the Institute. Section 5 presents potential applications of multilingual corpora in contrastive studies, using examples of the vocative case in Polish, Bulgarian and Lithuanian. The issues in focus are illustrated with examples extracted from the corpora under discussion.